Safety analysis, association with response and previous treatments of everolimus and exemestane in 181 metastatic breast cancer patients: A multicenter Italian experience. (October 2016) - Moscetti, L.; Vici, P.; Gamucci, T.; Natoli, C.; Cortesi, E.; Marchetti, P.; Santini, D.; Giuliani, R.; Sperduti, I.; Mauri, M.; Pizzuti, L.; Mancini, M.L.; et al.
Abstract: Purpose: The everolimus and exemestane combination represents a treatment option for the endocrine sensitive metastatic breast cancer (MBC) patients. The toxicity profile reported in the Bolero 2 trial showed the feasibility in the selected patients. Few data are available for the unselected population. Methods: In order to evaluate the safety in the unselected population of the clinical practice and to evaluate a possible association of toxicities with previous treatments, clinical data from 181 consecutive patients were retrospectively collected. Results: Due to toxic events, everolimus dosage was reduced to 5 mg in 27% of patients. No association was found in the analysis between toxicity and number of prior therapies, neither between toxicity and response. In the multivariate analysis the previous exposure to anthracyclines for advanced disease represents the only predictive factor of developing grade ≥2 toxicity (OR = 2.85 CI 95% 1.07–7.59, p = 0.036). Conclusions: The association of everolimus and exemestane has confirmed to be a safe and effective treatment for endocrine sensitive MBC patients even in routine clinical practice. The rate of treatment discontinuation due to toxicity is low and none association between previous number of treatments and response or between toxicity and response was found. Highlights: EVE and EXE combination represents a novel therapy for advanced breast cancer. Evaluations of toxicities in unselected patients are of interest. Retrospective analysis in unselected patients has been conducted. No association between toxicity and previous treatments has been found.